2017
DOI: 10.1097/md.0000000000006333
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic performance of perfusion MRI for differentiating glioma recurrence from pseudoprogression

Abstract: Background:The purpose of this meta-analysis was to evaluate the diagnostic accuracy of perfusion magnetic resonance imaging (MRI) as a method for differentiating glioma recurrence from pseudoprogression.Methods:The PubMed, Embase, Cochrane Library, and Chinese Biomedical databases were searched comprehensively for relevant studies up to August 3, 2016 according to specific inclusion and exclusion criteria. The quality of the included studies was assessed according to the quality assessment of diagnostic accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
(41 reference statements)
2
25
0
1
Order By: Relevance
“…While most previous studies have retrospectively compared diffusion and perfusion properties of pseudoprogression and true progression groups at the time of radiologic progression, 7,9,36,38,39 our results show post-RT changes in ADC histograms that precede radiologic progression and could be used to predict pseudoprogression. A recent report by Calmon et al 37 found differences in post-RT changes in DSC perfusion between pseudoprogression and true progression groups, confirming the usefulness of looking at post-RT changes in DIPG as a predictive radiologic marker of pseudoprogression.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…While most previous studies have retrospectively compared diffusion and perfusion properties of pseudoprogression and true progression groups at the time of radiologic progression, 7,9,36,38,39 our results show post-RT changes in ADC histograms that precede radiologic progression and could be used to predict pseudoprogression. A recent report by Calmon et al 37 found differences in post-RT changes in DSC perfusion between pseudoprogression and true progression groups, confirming the usefulness of looking at post-RT changes in DIPG as a predictive radiologic marker of pseudoprogression.…”
Section: Discussionmentioning
confidence: 63%
“…Poly (adenosine diphospate ribose) polymerase (PARP) inhibitors such as veliparib have been shown to overcome TMZ resistance while also increasing radiosensitivity. 4,5 Advanced ADC histogram metrics have been shown to correlate with survival 6 in DIPG, whereas perfusion and permeability metrics have shown associations with survival as well as pseudoprogression [7][8][9] in pediatric and adult gliomas. We therefore explored the utility of these imaging metrics to predict pseudoprogression versus early true progression.…”
mentioning
confidence: 99%
“…) than treatment effects (Fig. ) . rCBV is high in tumor, as it is reflective of the tumor hyperperfusion volume.…”
Section: Pseudoprogressionmentioning
confidence: 92%
“…2). 30,32,33 rCBV is high in tumor, as it is reflective of the tumor hyperperfusion volume. However, the optimum rCBV threshold for differentiating between tumor and treatment effects varies significantly between studies (range 0.71-3.7).…”
Section: Pseudoprogressionmentioning
confidence: 99%
“…12 Advanced imaging modalities (e.g., perfusion MRI, diffusion tensor imaging, and dynamic susceptibility contrast MRI) are currently under clinical investigation in an attempt to improve the diagnostic accuracy of identifying pseudoprogression. [53][54][55] Taken together, pseudoprogression likely represents a unique scenario encountered in patients with malignant glioma treated with radiation and chemotherapy. The pathophysiology of pseudoprogression is not well understood, and the clinical and radiographic course may be different from what is described for delayed onset of cerebral radiation necrosis.…”
Section: Pseudoprogressionmentioning
confidence: 99%